5-ALA based photodynamic management of glioblastoma - Rühm, Adrian; Stepp, Herbert; Beyer, Wolfgang; Hennig, Georg; Pongratz, Thomas; Sroka, Ronald; Schnell, Oliver; Tonn, Jörg Christian; Kreth, Friedrich Wilhelm (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2014)
Objective: Improvement of the clinical outcome of glioblastoma (GBM) patients by employment of fluorescence and photosensitization on the basis of 5-aminolevulinic acid (5-ALA) induced protoporphyrin IX (PpIX). Methods: In this report the focus is laid on the use of tumor selective PpIX fluorescence for stereotactic biopsy sampling and intra-operative treatment monitoring. In addition, our current concept for treatment planning is presented. For stereotactic interstitial photodynamic therapy (iPDT), radial diffusers were implanted into the contrast enhancing tumor volume. Spectroscopic measurements of laser light transmission and fluorescence between adjacent fibers were performed prior, during and post PDT. Results: PpIX concentrations in primary glioblastoma tissue show high intra-and inter-patient variability, but are usually sufficient for an effective PDT. During individual treatment attempts with 5-ALA based GBM-iPDT, transmission and fluorescence measurements between radial diffusers gave the following results: 1. In some cases, transmission after PDT is considerably reduced compared to the value before PDT, which may be attributable to a depletion of oxygenated hemoglobin and/or diffuse bleeding. 2. PpIX fluorescence is efficiently photobleached during PDT in all cases. Conclusion: iPDT with assessment of PpIX fluorescence and photobleaching is a promising treatment option. Individualization of treatment parameters appears to bear a potential to further improve clinical outcomes. © 2014 SPIE.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Aminolevulinic acid; glioblastoma multiforme; glioma; photobleaching; photodynamic therapy; stereotactic biopsy